2012
DOI: 10.1159/000331895
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Effect of Prolactin-Induced Protein

Abstract: Prolactin-induced protein (PIP) has been shown to bind to CD4 and is speculated to block CD4-HLA-DR interaction. However, the immunomodulatory effect of PIP on chronic allergic contact dermatitis (ACD) remains to be elucidated. The aim of this work was to define the role of PIP during the immunoresponse. Using an oxazolone-induced mouse chronic ACD model, expression of PIP was immunohistologically examined. Furthermore, effects of continued exposure of a peptide mimicking the major binding site of PIP (amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…We also found that the plasma prolactin-induced protein (PIP) levels were higher in T2DM patients with nephropathy. PIP has been implicated in immunosuppressive effects [ 18 ]. This suggests that PIP may act an immunosuppressive biomarker for T2DM in response to microvascular inflammation in T2DM with nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the plasma prolactin-induced protein (PIP) levels were higher in T2DM patients with nephropathy. PIP has been implicated in immunosuppressive effects [ 18 ]. This suggests that PIP may act an immunosuppressive biomarker for T2DM in response to microvascular inflammation in T2DM with nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin has a suppressive effect on inflammation [34]. Thus, the presence of increased serum prolactin levels in lactating rats may be associated with the attenuation of body temperature observed in lactating LPS-treated females compared with virgin saline-treated females.…”
Section: Discussionmentioning
confidence: 99%
“…PIP is an immunosuppressive molecule. 17,18 Differentially expressed genes in responders to fumaric acid esters…”
Section: Differentially Expressed Genes In the Skin Of Patients With ...mentioning
confidence: 99%